(untitled) (Altre Modernità, 2021)
A director, a successful journalist (working for The Daily Telegraph and The Independent), the author of two best-selling novels which consecrated her fame as an artist (Seahorses, 1997, and Too Fast to Live, published three years later), for the past ten years, Bidisha has devoted her talent to creating narratives that mix fictional and nonfictional elements (namely testimonies and reports). After Venetian Masters (2008), an autobiographical work where she revealed the cultural biases behind the seemingly impeccable façade of Venetian society, Bidisha seemingly started a project aimed at the inclusion of those who are commonly marginalized. Indeed, she is engaged in metaphorically dismantling walls, which may be either real and tangible, or invisible, such as those that prevent the refugees in London from being properly acknowledged. By focusing on Beyond the Wall: Writing a Path through Palestine (2012) and Asylum and Exile: The Hidden Voices of London (2014), this essay sets out to investigate the strategies employed by the writer to document what walls normally hide, thus restoring the dignity of precarious lives, striving to resist cultural annihilation.